School Attendance and Child Labor in Ecuador - Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2014)
The author uses the Ecuador Living Standards and Measurement Surveys (LSMS 1998 and 1999) to analyze the characteristics and determinants of child labor and schooling. She shows how interventions at the level of adults affect child labor and school enrollment. For example, an employment policy encouraging employment in the formal modern sector reduces child labor and increases schooling. In rural areas, a wage policy (increase in the wage of the household head) has positive implications for the children, while it is less effective in urban areas.